The Influence Of Housing Density, History Of Contact With Positive TB Cases, And BCG Immunization History On The Occurrence Of Pulmonary Tuberculosis In Productive Age Individuals - Hayati, Umratun; Sulistiyowati, Anisa Nanang (Sean Institute, 2024)
This study aims to analyze the effects of housing density, contact history with pulmonary tuberculosis (TB) patients, and BCG immunization history on the incidence of pulmonary tuberculosis among the productive age group at the Sriwini Community Health Center, Nabire Regency, Central Papua Province, in 2024. This research employs an analytical case-control study design. Data were collected through interviews and medical records of pulmonary TB patients at the community health center.The analysis results indicate that housing density does not have a significant effect on the incidence of pulmonary tuberculosis (P-Value = 1.000), and there is no significant effect of contact history with positive TB patients on pulmonary TB incidence (P-Value = 0.350). However, BCG immunization history was found to have a significant effect on the incidence of pulmonary tuberculosis (P-Value = 0.000). The study concludes that while housing density and contact history do not significantly affect the incidence, BCG immunization history plays an important role in preventing pulmonary tuberculosis among the productive age group in the region.The data collection method relies on interviews and medical records, which depend on the accuracy of information provided by respondents and the quality of medical documentation, potentially leading to information bias. This study contributes to reproductive health knowledge and serves as a reference for preventing and addressing TB health issues in the productive age group.